2018
DOI: 10.1097/md.0000000000012666
|View full text |Cite
|
Sign up to set email alerts
|

New vertebral fractures after osteoporotic vertebral compression fracture between balloon kyphoplasty and nonsurgical treatment PRISMA

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 45 publications
(62 reference statements)
0
39
0
1
Order By: Relevance
“…Vertebra compression fractures were caused by trauma of the spine, osteoporotic degeneration, metastatic disease, or primary tumor. [1,2,5,21] Vertebra compression fracture can lead to chronic back pain in 84% of symptomatic patients, [22] increased incidence of new vertebra compression fracture, [1,15] deformity of kyphosis, loss of mobility and pulmonary dysfunction. [23,24] As a result, mortality is also higher.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vertebra compression fractures were caused by trauma of the spine, osteoporotic degeneration, metastatic disease, or primary tumor. [1,2,5,21] Vertebra compression fracture can lead to chronic back pain in 84% of symptomatic patients, [22] increased incidence of new vertebra compression fracture, [1,15] deformity of kyphosis, loss of mobility and pulmonary dysfunction. [23,24] As a result, mortality is also higher.…”
Section: Discussionmentioning
confidence: 99%
“…New vertebral fracture after PVP in osteoporosis patients is also a common complication. [1,15] Uppin et al [15] reported that two-thirds of new fractures occur in the vertebrae adjacent to those previously treated. Wasnich et al [28] explained the reason for new fractures was probably because deformity and kyphosis vary the vectors of the forces which were in action throughout the spine after a vertebral compression fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Short-term (eg pain relief, restoration of mechanical stability, mobility improvement and fracture healing) and long-term achievements (eg progressive QOL improvement and prevention of NVCFs) need to be realized in strategies for patients who suffered osteoporotic vertebral compression fractures (OVCFs). 2,3 Vertebral augmentation procedures (VAP), ie percutaneous vertebroplasty (PVP) and/or PKP, is a minimally invasive therapy adopted in the treatment of OVCFs with the aim of prior pain alleviation by stabilizing the vertebral fracture and recovery of function by restoring vertebral body height (VBH). 4 Literature reported that PVP/PKP quickly restored patients' walking ability soon after operation and improved QOL in the early stage of OVCFs.…”
mentioning
confidence: 99%